Association between estimated glucose disposal rate and incident cardiovascular disease in a population with Cardiovascular-Kidney-Metabolic syndrome stages 0–3: insights from CHARLS - Tan, Ziyi; Zhou, Dayong; Tang, Yao; Huo, Guijun (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveEstimated glucose disposal rate (eGDR) is a reliable marker of insulin resistance (IR), which has been proven to be strongly linked to cardiovascular and renal diseases. However, the link between eGDR and the occurrence of cardiovascular disease (CVD) in individuals exhibiting Cardiovascular-Kidney-Metabolic (CKM) syndrome stages 0–3 remains ambiguous.MethodsThe data employed in this investigation was procured from the China Health and Retirement Longitudinal Study (CHARLS). The outcome of this study was CVD events, which include heart disease and stroke. Cox regression models and restricted cubic spline (RCS) were employed to investigate the association between eGDR and CVD risk among individuals with CKM syndrome stages 0–3.ResultsThis investigation encompassed 6,539 subjects, and 54.43% were female. 1,656 (26.04%) CVD events were recorded. After fully adjusting for covariates, each 1-unit increase in eGDR was linked to a 9% diminish in CVD risk (HR: 0.91, 95% CI: 0.88, 0.93). In comparison to the bottom quartile of eGDR, the adjusted HRs (95% CIs) for the second to fourth quartiles were 0.73 (95% CI: 0.64, 0.83), 0.65 (95% CI: 0.56, 0.76), and 0.56 (95% CI: 0.47, 0.66), respectively. The RCS curves revealed a substantial negative nonlinear association between eGDR and CVD events among participants with CKM syndrome stages 0–3 (P-value < 0.001 and P for nonlinear = 0.009).ConclusionsIn a population with CKM stages 0–3, a significant negative nonlinear relationship was observed between eGDR and CVD risk, suggesting that eGDR might function as a useful metric for evaluating CVD risk.